Design, Development and Evaluation of Tetracycline Controlled Release Microspheres - Das, Sudipta; Ghosh, Baishali; Basu, Surita; Ghosh, Biswajit; Nag, Sanjoy (Asian Journal of Pharmaceutical Research and Development, 2023)
Microsphere drug delivery methods have been used to boost efficacy, reduce toxicity, and improve patient compliance. Additional benefits of using microspheres to deliver medications include controlled drug release, improved bioavailability, and targeted drug delivery to the desired location. In order to achieve the required therapeutic effect, hydroxypropyl methyl cellulose K4M and sodium alginate are used as a polymer in microsphere delivery system and different concentration of aluminium chloride is used as cross linking agent. The advantage of microsphere formulations over traditional tablet or capsule formulations is that they increase the surface area exposed to the absorption site, boosting medication absorption and reducing drug dose frequency. Tetracycline is a broad-spectrum antibiotic that is frequently used to treat illnesses like pneumonia and respiratory tract infections. The encapsulation effectiveness, particle size, in -vitro release analysis and release kinetics of the microsphere formulations was assessed.